Study on the patterns and trend in contraceptive use in South-South and North-Western zones of Nigeria: 2003–2011 - Ezire O; Idogho O; Theophilus A; Ikani S; Oluigbo O (Dove Medical Press, 2014)
Onoriode Ezire,1 Omokhudu Idogho,2 Ajibade Theophilus,3 Samuel Ikani,4 Obi Oluigbo1 1Research and Evaluation Division, Society for Family Health, Nigeria; 2Enhancing Nigeria’s Response to HIV and AIDS Programme, Abuja, Nigeria; 3Population Council, Abuja, Nigeria; 4Strengthening HIV Prevention Services for Most-At-Risk Populations, Abuja, Nigeria Background: Nigeria is ranked 13th among countries with the highest fertility rates in the world – 5.7 births per woman on average. Age specific fertility rates are as high as 121 and 225 per 1,000 for ages 15–19 and 20–24 years, respectively. Only 9.7% of currently married women in Nigeria use modern methods of family planning (FP). This figure, however, does not reveal important age, geographical, or educational differences in Nigeria. The overall purpose of the study is to establish hidden demographic factors that enhance usage of modern methods of FP. Methods: Data for this study were obtained from four waves of the National and State Specific HIV and AIDS, Reproductive and Child Health Survey – NARHS/SARHS (2003, 2005, 2007, and 2011). Data were collected among men and women of reproductive age in the 36 states of Nigeria including Federal Capital Territory (FCT). For the analysis, the study was however limited to North West and South-South zones of Nigeria. Bivariate and multiple logistic regression was performed using SPSS version 20. Results: Use of modern methods of FP has increased over time with an average annual increase of 0.47%. Different age groups, zones, and educational attainment prefer different modern methods of FP. Of all users of modern methods of FP, long lasting methods account for just 3% while condoms account for as high as 58%. Eighty-six percent of sexually active never married women use condoms for FP. Women in South-South Nigeria are over three times and five times more likely to use a modern method of FP and a condom, respectively. Conclusion: Demographic characteristics significantly determine the patterns, trend, and use of modern methods of FP in the studied states. Bearing in mind identified challenges associated with short term methods, innovative ways should be identified to scale up use of long lasting methods. The study corroborates recommendations of previous studies promoting female child education as a way to improve use of modern methods of contraception. Keywords: family planning, contraceptive use, Nigeria, condom, injectables